SARS-CoV-2 Nsp6-Omicron causes less damage to the Drosophila heart and mouse cardiomyocytes than ancestral Nsp6 - Jun-yi Zhu; Jin-Gu Lee; Guanglei Wang; Jianli Duan; Joyce van de Leemput; Hangnoh Lee; Wendy Wenqiao Yang; Zhe Han (Communications Biology)
Abstract A few years into the COVID-19 pandemic, the SARS-CoV-2 Omicron strain rapidly becomes and has remained the predominant strain. To date, Omicron and its subvariants, while more transmittable, appear to cause less severe disease than prior strains. To study the cause of this reduced pathogenicity we compare SARS-CoV-2 ancestral Nsp6 with Nsp6-Omicron, which we have previously identified as one of the most pathogenic viral proteins. Here, through ubiquitous expression in Drosophila, we show that ancestral Nsp6 causes both structural and functional damage to cardiac, muscular, and tracheal (lung) tissue, whereas Nsp6-Omicron has minimal effects. Moreover, we show that ancestral Nsp6 dysregulates the glycolysis pathway and disrupts mitochondrial function, whereas Nsp6-Omicron does not. Through validation in mouse primary cardiomyocytes, we find that Nsp6-induced dysregulated glycolysis underlies the cardiac dysfunction. Together, the results indicate that the amino acid changes in Omicron might hinder its interaction with host proteins thereby minimizing its pathogenicity.